Evaluation of the entrepreneurial potential of the clinical veterinarians using the Turkish version of the entrepreneurial potential assessment inventory (EPAI-TR) - Sipahi, C.; Akin, A. C.; Mat, B.; Cevrimli, M. B.; Arikan, M. S.; Tekindal, M. A. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2024)
The present study aimed to determine the unique values of the entrepreneurial potential of clinical veterinarians and to evaluate this potential by using a reliable and valid measurement tool. The study material was the data obtained from a survey conducted between May 2020 and April 2021 that included 343 veterinarians who were actively working in a veterinarian clinic/outpatient clinic. The Turkish version of the Entrepreneurial Potential Assessment Inventory was used to collect the data. On the basis of the results of the explanatory factor analysis, confirmatory factor analysis, and improvement (modification) indices calculated from the survey data, a 7-factor structure was obtained. According to the results of the entrepreneurial potential scale for clinical veterinarians, the following sub-dimensions of the scale were listed according to their contribution to the total variance explained: effective communicative leadership, strategic resource development, self-efficacy, innovative creativity, resilience-strength, motivation for economic freedom, and risk-taking propensity. This ranking reveals a tendency to possess these characteristics in Turkiye for entrepreneurship potential regardless of the profession. In light of the obtained data, it is recommended to provide clinical veterinarians with training on the topics of forming social networks, taking responsibility, and developing emotional intelligence, which is not included in the scale, as well as to instigate the desire to become independent and economically motivated to improve their entrepreneurial potential.
Avaliação do potencial empreendedor dos veterinários clínicos usando a versão turca do inventário de avaliação do potencial empreendedor (EPAI-TR)
Keywords: entrepreneurial potential; EPAI-TR; veterinary clinic enterprise